University Orientation and Tutories: Student’s Notion about IT - Villamil, Kasandra Vanessa Saldarriaga; Almedina, Maria Isabel Amor (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the work is to analyze the notion of first-year students of the careers taught at the Faculty of Humanistic and Social Sciences of the Universidad Técnica de Manabí, on the orientation and tutoring at the level of higher education. The work offers an analysis of the functioning of the university tutoring space, based on the criterion that students have of new income on the relevance of the tutorial care process, viewed from the institutional part and the criterion of the students themselves. To do this, a bibliographic consultation was carried out that allowed analyzing theoretically the tutorial spaces from its emergence until the present date. It shows the results of a survey carried out on the students, where you could check the high concept that they have the realization of the tutorial spaces, as well as some difficulties that exist for the fulfillment of the activity by the teachers who perform i.